GABAB Receptor Agonist R-Baclofen Reverses Altered Auditory Reactivity and Filtering in the Cntnap2 Knock-Out Rat - Möhrle, Dorit; Wang, Wenxuan; Whitehead, Shawn N.; Schmid, Susanne (Frontiers in Integrative Neuroscience, 2021)
Altered sensory information processing, and auditory processing in particular, is a common impairment in individuals with autism spectrum disorder (ASD). One prominent hypothesis for the etiology of ASD is an imbalance between neuronal excitation and inhibition. The selective GABAB receptor agonist R-Baclofen has been shown previously to improve social deficits and repetitive behaviors in several mouse models for neurodevelopmental disorders including ASD, and its formulation Arbaclofen has shown to ameliorate social avoidance symptoms in some individuals with ASD. The present study investigated whether R Baclofen can remediate ASD-related altered sensory processing reliant on excitation/inhibition imbalance in the auditory brainstem. To assess a possible excitation/inhibition imbalance in the startle-mediating brainstem underlying ASD-like auditory-evoked behaviors, we detected and quantified brain amino acid levels in the nucleus reticularis pontis caudalis (PnC) of rats with homozygous loss-of-function mutation in the ASD-linked gene Contactin-associated protein-like 2 (Cntnap2) and their wildtype littermates using Matrix-Assisted Laser Desorption Ionization Mass Spectrometry (MALDI MS). Abnormal behavioral read-outs of brainstem auditory signaling in Cntnap2 KO rats were accompanied by increased levels of GABA, glutamate, and glutamine in the PnC. We then compared the effect of R-Baclofen on behavioral read-outs of brainstem auditory signaling in Cntnap2 KO and wildtype rats. Auditory reactivity, sensory filtering and sensorimotor gating were tested in form of acoustic startle response input-output functions, short-term habituation and prepulse inhibition before and after acute administration of R Baclofen (0.75, 1.5, and 3 mg/kg). R-Baclofen treatment improved disruptions in sensory filtering in Cntnap2 KO rats and suppressed exaggerated auditory startle responses, in particular to moderately loud sounds. Lower ASR thresholds in Cntnap2 KO rats were increased in a dose-dependent fashion, with the two higher doses bringing thresholds close to controls, whereas shorter ASR peak latencies at threshold were further exacerbated. Impaired prepulse inhibition increased across various acoustic prepulse conditions after administration of R-Baclofen in Cntnap2 KO rats, whereas R-Baclofen did not affect prepulse inhibition in wildtype rats. Our findings suggest that GABAB receptor agonists may be useful for pharmacologically targeting multiple aspects of sensory processing disruptions involving neuronal excitation/inhibition imbalances in ASD.